PERAN PRODUCT QUALITY, INFORMATION QUALITY DENGAN MEDIASI TRUST TERHADAP REPURCHASE INTENTION PADA MITRA UMKM GO-FOOD DI SURAKARTA - prastiwi, septi kurnia; Rabia, Rabia; Bagus, Renanda (Universitas Muhammadiyah Surakarta, 2019)
This study aims to examine the factors that may affect repurchase intention for Go food product. Two variables suspected to affect the repurchase intention are product quality and information quality with trust as mediation. The design of this study is survery method with a population of go jek user in Solo, with sample size of 100 respondents, the sampling methods purposive sampling a questionnaire with 12 indicators questions. Test results validity, reliability and classic assumption test support for continuing research. Path analysis get the result that variable product quality not significantly affect trust and repurchase intention, but variable information quality can affect positively and significantly related to trust and the dependent variable repurchase intention. To examine variable trust can be mediator variable product quality Â to repurchase intention, evidence by sobel test and get the result that variable trust significantly as mediator variable.